دور المدرسة في تحقيق الضبط الاجتماعي - مأمون، علي, زواري، أحمد الصادق (جامعة الوادي university of Eloued, 2020)
Résumé : Firstly,our study aimes to know methods of social control in educational institutions and highlighting the important role that the school plays in achieving social control among secondary school students ,and knowing the needs of pupils inside school. However,starting by asking the following essential question Does the school have a role in achieving social control among secondary school students? Sub-questions branch out from it, the most important of which are:  Does the relationship between the principal and the student contribute to achieving social control among secondary school students?  Does the relationship between administration and the student contribute to achieving social control among secondary school students?  Does the relationship between the school and vocational guidance counselor and the student contribute to achieving social control among secondary school students?  Does the relationship between the teacher and the student contribute to achieving social control among secondary school students? Finally,our study was relied on the descriptive approach ,and reveals the relationship of the school’s role in achieving social control. Our study was supposed to be conducted on a sample of 100 students who study at Ourmes High School
دراسة ميدانية بثانوية شوية الجباري بورماس ولاية الوادي
مذكرة ماستر في علم الإجتماع تخصص علم إجتماع التربية
Keywords: المدرسة، الضبط الإجتماعي; École, contrôle social; School, social control